2021
DOI: 10.1017/s1041610221000521
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom and fluid intelligence are dissociable in healthy older adults

Abstract: Objectives: The relationship between wisdom and fluid intelligence (Gf) is poorly understood, particularly in older adults. We empirically tested the magnitude of the correlation between wisdom and Gf to help determine the extent of overlap between these two constructs. Design: Cross-sectional study with preregistered hypotheses and well-powered analytic plan (https://osf.io/h3pjx). Setting: Memory and Aging Center at the University of California San Francisco, located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Yet, wiser fathers and mothers might place less emphasis on intellectual development than on growth in social intelligence and emotional competence, because they know that intelligence by itself is insufficient for wisdom development. Prior research found no or only a weak correlation between measures of wisdom and intelligence, particularly in adulthood (Ardelt, Gerlach et al, 2018;Glück et al, 2013;Lindbergh et al, 2021;Staudinger & Glück, 2011a;Staudinger, Lopez, & Baltes, 1997;Staudinger, Maciel, Smith, & Baltes, 1998;Staudinger & Pasupathi, 2003). A recent study suggests that intelligence is a necessary but not sufficient condition for wisdom development as many individuals with high intelligence scores are not wise (Glück & Scherpf, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Yet, wiser fathers and mothers might place less emphasis on intellectual development than on growth in social intelligence and emotional competence, because they know that intelligence by itself is insufficient for wisdom development. Prior research found no or only a weak correlation between measures of wisdom and intelligence, particularly in adulthood (Ardelt, Gerlach et al, 2018;Glück et al, 2013;Lindbergh et al, 2021;Staudinger & Glück, 2011a;Staudinger, Lopez, & Baltes, 1997;Staudinger, Maciel, Smith, & Baltes, 1998;Staudinger & Pasupathi, 2003). A recent study suggests that intelligence is a necessary but not sufficient condition for wisdom development as many individuals with high intelligence scores are not wise (Glück & Scherpf, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Our study provides support for the claim that wisdom may protect against loneliness in older adults. The skills embodied by the construct of wisdom can possibly be harnessed and cultivated to develop effective interventions for older adults at risk of loneliness, especially given their dissociation from age-dependent fluid intelligence (Lindbergh et al, 2021). Additional research is needed to determine directional causality in the relationship between wisdom and loneliness and whether these associations hold in demographically diverse adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative and qualitative research indicates that wisdom may buffer against loneliness and mitigate some of its effects (Lee et al, 2019;Morlett Paredes et al, 2021), although causality has yet to be determined. Wisdom is also dissociated from fluid intelligence-which declines in older age, suggesting that wisdom can be maintained as a lifelong skillset (Lindbergh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they adopt an automated and accepting approach toward their experiences, primarily engaging bottom-up processes. However, given that deficits in older adults often center around activities dependent on the prefrontal cortex, such as fluid intelligence (Lindbergh et al, 2021), mindfulness-based interventions designed to enhance attention monitoring can serve as valuable strategies, both in a preventive capacity and potentially as a mitigating measure against metacognitive decline. The primary aim of this research was to explore the relationship between trait mindfulness and metacognitive efficiency in older adults, with a broader goal of advancing the empirical understanding of the interplay between these constructs.…”
Section: Introductionmentioning
confidence: 99%